Quality of life and mental well-being as preventive factors towards the occurrence of juvenile delinquency among Malaysian adolescents - Mimi, Fitriana; Wood, Megan; Wu, Shin Ling *; Ching, Sin Siau (Silpakorn University Research Innovation and Creativity Administration Office, 2022)
Juvenile delinquency is a complex problem that affects the individual's social community and eventually the society as a whole. Despite the common knowledge and understanding of risk factors, the identified number of juvenile delinquency cases in Malaysia are at high influx with interventions to decrease its occurrence indicating the possible predicting preventive factors that have yet been investigated. Therefore, this paper aimed to compare the occurrence of juvenile delinquency in adolescents, in Kuala Lumpur, within the range of low and high quality of life as well as poor and good mental well-being. A causal-comparative design was used to identify the predicting preventive factors for juvenile delinquency among adolescents through the administration of Family Quality of Life Scale (FQOL), Warwick-Edinburgh Mental Well-being Scale (WEMWBS), and Self-Reported Delinquency to 224 respondents using a purposive sampling technique. Independent Samples t-test revealed the significant differences between the low and high group of quality of life, poor and good mental well-being, and gender differences. The regression model showed mental well-being as a significant predictor to prevent the occurrence of juvenile delinquency among adolescents. Implications of these findings contributed to the development of modules and interventions of preventing strategies for the delinquent behaviors. © 2022 Asociacion Paleontologica Argentina. All rights reserved.